The feasibility and acceptability of assessing and managing sarcopenia and frailty among older people with upper limb fracture. (30th December 2021) - Ibrahim, Kinda; Mullee, Mark A; Cox, Natalie; Russell, Cynthia; Baxter, Mark; Tilley, Simon; Yao, Guiqing Lily; Zhu, Shihua; Roberts, Helen C
Abstract: Background: sarcopenia and frailty are associated with increased risk of falls and fractures. This study evaluated the feasibility of assessing sarcopenia and frailty among older people attending fracture clinics. Methods: patients aged 65+ years with an arm fracture attending fracture clinics in one UK city were recruited. Sarcopenia was assessed using gait speed, grip strength, skeletal muscle mass index SMI, SARC-F questionnaire and the European Working Group on Sarcopenia in Older People (EWGSOP) I and II criteria. Frailty was assessed using Fried Frailty Phenotype (FFP), FRAIL scale, PRISMA-7, electronic Frailty Index (e-FI), Clinical Frailty Score (CFS) and Study of Osteoporotic Fracture. The sensitivity and specificity of each tool was calculated against the EWGSOP II criteria (sarcopenia) and FFP (frailty). Patients identified to have either condition were referred for Comprehensive Geriatric Assessment (CGA). Interviews with 13 patients and nine staff explored the acceptability of this process. Results: hundred patients (Mean age 75 years) were recruited. Most sarcopenia and frailty assessments were quick with complete data collection and were acceptable to patients and staff. Sarcopenia was identified among 4–39% participants depending on the tool and frailty among 9–25%. Both conditions were more common among men than women with all tools. The SARC-F and PRISMA-7 had the best sensitivity (100 and 93%, respectively) and specificity (96 and 87%). CGA among 80% of referred participants led to three interventions per participant (e.g. medication changes and investigations). Conclusion: SARC-F and PRISMA-7 are recommended for use in fracture clinics to screen for sarcopenia and frailty.